Volume overload in hemodialysis: diagnosis, cardiovascular consequences, and management. Issue 12 (13th November 2020) - Loutradis, Charalampos; Sarafidis, Pantelis A; Ferro, Charles J; Zoccali, Carmine
Abstract: Volume overload in haemodialysis (HD) patients associates with hypertension and cardiac dysfunction and is a major risk factor for all-cause and cardiovascular mortality in this population. The diagnosis of volume excess and estimation of dry weight is based largely on clinical criteria and has a notoriously poor diagnostic accuracy. The search for accurate and objective methods to evaluate dry weight and to diagnose subclinical volume overload has been intensively pursued over the last 3 decades. Most methods have not been tested in appropriate clinical trials and their usefulness in clinical practice remains uncertain, except for bioimpedance spectroscopy and lung ultrasound (US). Bioimpedance spectroscopy is possibly the most widely used method to subjectively quantify fluid distributions over body compartments and produces reliable and reproducible results. Lung US provides reliable estimates of extravascular water in the lung, a critical parameter of the central circulation that in large part reflects the left ventricular end-diastolic pressure. To maximize cardiovascular tolerance, fluid removal in volume-expanded HD patients should be gradual and distributed over a sufficiently long time window. This review summarizes current knowledge about the diagnosis, prognosis and treatment of volume overload in HD patients.